Magneto‐Mechanical Metamaterials with Widely Tunable Mechanical Properties and Acoustic Bandgaps. (8th October 2020) - Montgomery, S. Macrae; Wu, Shuai; Kuang, Xiao; Armstrong, Connor D.; Zemelka, Cole; Ze, Qiji; Zhang, Rundong; Zhao, Ruike; Qi, H. Jerry
Abstract: Mechanical metamaterials are architected manmade materials that allow for unique behaviors not observed in nature, making them promising candidates for a wide range of applications. Existing metamaterials lack tunability as their properties can only be changed to a limited extent after the fabrication. Herein, a new magneto‐mechanical metamaterial is presented that allows great tunability through a novel concept of deformation mode branching. The architecture of this new metamaterial employs an asymmetric joint design using hard‐magnetic soft active materials that permits two distinct actuation modes (bending and folding) under opposite‐direction magnetic fields. The subsequent application of mechanical compression leads to the deformation mode branching where the metamaterial architecture transforms into two distinctly different shapes, which exhibit very different deformations and enable great tunability in properties such as mechanical stiffness and acoustic bandgaps. Furthermore, this metamaterial design can be incorporated with magnetic shape memory polymers with global stiffness tunability, which also allows for the global shift of the acoustic behaviors. The combination of magnetic and mechanical actuations, as well as shape memory effects, impart wide tunable properties to a new paradigm of metamaterials. Abstract : A new magneto‐mechanical metamaterial permits great shape and multi‐physical property tunability through a novel concept of deformation mode branching. This is achieved through an asymmetric joint design using hard‐magnetic soft active materials with coupled magneto‐mechanical actuation. The metamaterial design can be further incorporated with magnetic shape memory polymers for global tunability of physical properties.